Language practices in Indigenous language Public Service Radio in South Africa - Masuku, Matsobane Lehlogonolo (Rhodes University, 2026)
This study interrogates the continuing privileging of colonial languages in the South African broadcast landscape, despite the South African Broadcasting Corporation (SABC)’s democratic commitment to foregrounding indigenous languages within the public sphere. It focuses on the implications for the way in which the history of South Africa’s language politics has contributed to the continued marginalisation of indigenous languages. It deals with this subject matter by means of a case study of Thobela FM, one of the SABC’s indigenous language stations which broadcasts in Sepedi. The study aims to gain insight into the experiences of staff at Thobela FM regarding changes in language practices at the station over time. It also explores how these experiences have been shaped by broader shifts in the history of language politics in South Africa. In order to establish a conceptual framework for this examination, the study draws on a review of literature dealing with history of the politics of language in South Africa. It does so by exploring debates that have formed part of that history and identifying key terms that have formed part of those debates. The study applies this framework to an exploration of the way staff at Thobela FM staff have experienced their own location within this broader history at different moments in time, drawing on biographic interviews with these individuals. Firstly, it examines the personal linguistic identities of the participants and the role of radio as a medium in their upbringings. Finally, it investigates their professional experience at Thobela FM. The analysis of the qualitative data was carried out through thematic analysis. The study concludes that the station has in fact made progress with the implementation of language practices that work against the marginalisation of Sepedi within South African broadcast landscape. Furthermore, it finds that multilingualism has always been a core tenet of the station, and that presenters, producers and programming staff have all played a part in the realisation of this vision.
a case study of Thobela FM
Keywords: Uncatalogued